The future of olive groves on sloping land and ex-ante assessment of cross compliance for erosion control - Graaff, Jan de (2010)
Under the past Common Agricultural Policy (CAP) olive oil subsidy regime, farmers were eligible for subsidies on the basis of the amount of olive oil they produced. This led to an intensification of production, particularly on flat land, and had inmost cases negative environmental effects, such as more soil erosion on sloping land and more pollution. With the decoupling of agricultural support under the newly established rules of the CAP, formalised in 2005, cross compliance measures have become obligatory. In this paper an ex-ante assessment is made of the application of cross compliance for soil erosion control (natural cover crops and terrace maintenance) in hilly and mountainous olive groves in Tr ´ as-os- Montes in Portugal. A linear programming model was developed to assess the various socio-economic and environmental effects of four different development scenarios for olive groves. The scenarios were developed on the basis of changing market prices, wage rates and subsidies; their effects included shifts towards intensification, abandonment and organic farming. Simulations considering a minimum return to labour constraint showed very high levels of abandonment, particularly in combination with cross compliance obligations. However, even without this minimum return to labour constraint, abandonment would reach more than 20% in three out of the four scenarios. The model showed that cross compliance obligations could be quite effective in reducing erosion, but that theywould depress income in all scenarios as a result of higher abandonment and lower percentage shifts towards intensive systems.